When Data Does Not Deliver: Rethinking Datafication in Global Higher Education - Komljenovic, Janja (International Higher Education, 2025)
<h3 id="in-higher-education-digital-data-is-seen-as-transformative-and-there-is-an-omnipresent-belief-in-its-value-however-digital-data-is-not-inherently-valuable-rather-it-needs-to-be-made-so-this-article-investigates-five-challenges-of-datafication-in-the-sector-addressing-common-misconceptions-it-advocates-for-slow-and-responsible-data-innovation-to-meet-the-sectors-evolving-needs" data-pm-slice="1 1 []">In higher education, digital data is seen as transformative, and there is an omnipresent belief in its value. However, digital data is not inherently valuable; rather, it needs to be made so. This article investigates five challenges of datafication in the sector, addressing common misconceptions. It advocates for slow and responsible data innovation to meet the sector’s evolving needs.